Physicochemical Properties of Apple Snail Protein Hydrolysate (Pila ampullacea) and its Potential as Flavor Enhancer - Erika Puspitasari; Dedin Finatsiyatull Rosida; Andre Yusuf Trisna Putra; Anugerah Dany Priyanto (Food, Agriculture and Natural Resources - NETWORKS, 2022)
ple snail is a source of animal protein that has a high enough protein. Protein can be hydrolyzed by natural proteases, which one is bromelain. Enzymatic hydrolysis can produce hydrolysates containing peptides and amino acids that contribute to umami taste. The purpose of this study was to determine the effect of hydrolysis time and bromelain concentration on the physicochemical properties of apple snail hydrolysate. The optimal result in this study were used as natural flavor enhancer. This study used a completely randomized design with two factors. Factor I was the hydrolysis time (6 hours, 12 hours, and 18 hours) and factor II was the concentration of the bromelain (5%, 10%, and 15%). Based on the results showed that apple snail hydrolysate was influenced by hydrolysis time and bromelain concentration. The optimal result in this study was 18 hour hydrolysis treatment with 15% bromelain enzyme concentration had a yield 68.16%, degree of hydrolysis 72.09%, soluble protein 9.03%, total peptide 10.84 mg/mL, and glutamic acid 107.47 ppm. The application of apple snail protein hydrolysate give characteristics of flavor enhancers as follows: soluble protein 7.76%, glutamic acid 99.42 ppm, solubility 94.79%, water absorption 5.80 mL/g, hedonic test color 4.10 (neutral), aroma 5.05 (like slightly), and taste 5.10 (like slightly).